Comparison of yeast (Saccharomyces cerevisiae) fermentation between honey and commercial sugars - Osman, Nur Atiqah (2015)
Background. Honey varies in color and flavour. Its composition also varies widely and depending largely on its floral sources. Because of honey’s complex and unusual composition, honey has its own properties that make it differ from all other sweetening agents. The purpose of this study was to compare sugar metabolism between selected honey samples from Malaysia and a few countries and commercial sugar by using Saccharomyces cerevisiae as a model organism. The significant differences in the sugar metabolism is important to predict honey as quality sugar sources compared to typical commercial sugar. Methodology. Forty-five samples of honey which have equivalent amount of sugar composition as three commercial sugars namely glucose, fructose, and sucrose that used as control were screen by using rapid fermentation techniques. The experiment is repeated with the aid of cultured yeast in order to validate the screened data using packed baker yeast ( S. cerevisiae ). Results. The comparison of glucose metabolized by yeast S. cerevisiae using rapid fermentation techniques were successfully proved that the fermentation in honey sugar and commercial sugar the yeast cells fermented honey sugar the most. Among the forty five samples of honey, honey tramp species ( sample 32 ) released the highest amount of carbon dioxide. Conclusion. The results found that the honey samples exhibited a significant differences in sugar metabolism between honey and commercialised sugar . It is also suggested that honey has the ability to reduce the blood glucose and might be suitable to be consumed by healthy and diabetic person.